2022
DOI: 10.1002/adsc.202101372
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Spirooxindole‐Benzo[d]oxazoles and Dihydrobenzofurans through Cycloaddition and Rearrangement of N‐Vinyl Nitrones and Arynes

Abstract: Various spirooxindole‐benzo[d]oxazoles and dihydrobenzofurans were prepared in good to excellent yields by [3+2] cycloaddition and selective rearrangement of N‐vinyl oxindole nitrones and arynes under transition metal‐free conditions. Experimental results showed that the substituent on the nitrone N‐vinyl group controlled the [1,3]‐ or [3,3]‐rearrangement of their cycloadduct owing to its steric effect. The present method features broad substrate scope, good functional group tolerance, controllable [1,3]‐ or [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…This cascade reaction is a new pathway in the synthesis of nitrogen-containing heterocyclic compounds via prepared by [3 + 2] cycloaddition and selective rearrangement of N-vinyl oxindole nitro compounds and benzynes compounds under transition-metal-free conditions in good to excellent yields (Scheme 17b). 81 Zhang et al developed a [3 + 2] cyclization/arylation of isatin N,N ′ -cyclic azomethine imine 1,3dipole with in situ generated benzyne to access 3,3-disubstituted oxindole scaffolds in moderate yields. The method could form various biologically active disubstituted oxindoles with simple and mild reaction advantages, practical and one-pot (Scheme 17c).…”
Section: [2 + 2] Cycloaddition Reactionmentioning
confidence: 99%
“…This cascade reaction is a new pathway in the synthesis of nitrogen-containing heterocyclic compounds via prepared by [3 + 2] cycloaddition and selective rearrangement of N-vinyl oxindole nitro compounds and benzynes compounds under transition-metal-free conditions in good to excellent yields (Scheme 17b). 81 Zhang et al developed a [3 + 2] cyclization/arylation of isatin N,N ′ -cyclic azomethine imine 1,3dipole with in situ generated benzyne to access 3,3-disubstituted oxindole scaffolds in moderate yields. The method could form various biologically active disubstituted oxindoles with simple and mild reaction advantages, practical and one-pot (Scheme 17c).…”
Section: [2 + 2] Cycloaddition Reactionmentioning
confidence: 99%
“…Indeed, this reaction is expected to afford benzene-fuzed nitrosoacetals 5 or 6 , which may serve as precursors of aminoalcohols 7 and 8 bearing a phenol moiety. Albeit cycloadditions of arynes with various N -oxide-based 1,3-dipoles (nitrones, 10 nitrile oxides, 11 heterocyclic N -oxides 12 ) have been extensively studied in recent years, nitronates remain unexplored in these reactions. In our recent communication, 13 we reported that the reaction of C(3) unsubstituted 5,6-dihydro-4 H -1,2-oxazine N -oxides 1 (R = H) with Kobayashi's aryne precursors 14 9 produced 3-(2-hydroxyaryl)-substituted 1,2-oxazines 10 , which were likely formed by a spontaneous fragmentation of the five-membered ring in the initially generated cycloadducts 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Intramolecular reactions include phenolic cyclization, [7] Claisen/cyclization sequence, [8] reductive Heck coupling, [9] and sigmatropic rearrangement [5e,10,11] . For intermolecular reactions, addition/cyclization, [12,13] oxidative coupling, [14] and cyclization/rearrangement sequence have been used [15] . Dearomative annulation using benzofuran as a substrate is one of the simplest strategies.…”
Section: Introductionmentioning
confidence: 99%